Contemporary authors. Volume 106 - 4 0 16; Locher, Frances Carol.;Conway, Martha G.; 5 (Detroit, Michigan : Gale Research Company, 1982)
Profiles writers of fiction, nonfiction, poetry, and drama; print, broadcast, and photojournalists; cartoonists; and other media figures who lived and wrote between 1900 and 1959, providing bibliographical and biographical information, including mailing addresses.
A bio-bibliographical guide to current writers in fiction, general nonfiction, poetry, journalism, drama, motion pictures, television, and other fields.
Includes bibliographical references and index.
Keywords: 2 -- 0; 6; Authors;Authors;Authors;Authors -- Biography.;Bio-bibliography.;Biography.;Bio-bibliography.; 20; 2